Three‐Dimensional Visualization of Subcellular Dynamics of Cancer Cell Destruction on Therapeutic Nanodrug Treatment. Issue 7 (25th April 2021) - Raveendran, Sreejith; Sen, Anindito; Maekawa, Toru; Kumar, D. Sakthi
Abstract : Ultrastructural visualization of targeted nanoparticles against its interactions with subcellular organelles through electron microscopy and its 3D rendering is always challenging. Mechanistic and conformational understandings of specific subcellular connections of novel smart nanocarriers with various intrinsic receptors of breast cancer cells are critical for the design and delivery of novel cancer therapeutics. Toxicological effects of gold nanocages, passivated with extremophilic polysaccharide, Mauran functionalized with 4‐hydroxytamoxifen and monoclonal antibody Pr1E11 result in downright decimation of subcellular organelles in breast cancer MCF7 cells resulting in parallel type I and type II cell deaths. Herein, the deleterious repercussions of the therapeutic gold nanocages (TANs) on the subcellular organelles of MCF7 cells are studied. Confocal and transmission electron microscopic images reveal significant localization of the TANs within the mitochondria, lysosomes, and autophagosomes leading to their destruction in a span of 96 h from their incubation. The 3D electron density maps of these subcellular organelles computed using images recorded by scanning block‐face electron and transmission electron microscopes reveal a previously unknown systemic degradation process of mitochondria and the structure of autolysosome. Together, this data fortifies the benefit of subcellular cancer targeting and multiple parallel damage explained through advanced electron microscopic visualization. Abstract : Ultra‐structural visualization of subcellular targeting and multiple parallel damage caused to mitochondria and lysosomes of breast cancer cells are studied using serial‐ block‐face scanning electron microscopy. Mechanistic and conformational understanding of specific subcellular connections of novel smart nanocarriers with various intrinsic receptors are critical for the design and delivery of novel cancer therapeutics.